Biomimetic synthesis of nanostructured SnO particles from Sn6O4(OH)4 in aqueous solution of gelatin. Issue 3 (28th November 2014) - Uchiyama, H.; Nakanishi, S.; Kozuka, H.
Abstract : Nanostructured SnO particles were produced by aging Sn6 O4 (OH)4 in aqueous solutions containing HCl and gelatin at 60 °C. Flower-like and spherical architectures consisting of radially-branched platy units were obtained by the addition of gelatin, where the branching of SnO crystals was promoted with decreasing pH value and with increasing gelatin contents. Abstract : Nanostructured SnO particles were produced by aging Sn6 O4 (OH)4 in aqueous solutions containing HCl and gelatin at 60 °C, where the morphologies of the SnO products depended on the pH value and the gelatin concentration of the solutions. Flower-like and spherical architectures consisting of radially-branched platy units were obtained by the addition of gelatin, where the branching of SnO crystals was promoted with decreasing pH value and with increasing gelatin contents. The branched structures thus obtained could be formed via diffusion-controlled growth of SnO crystals in viscous solutions.